Experimental study on transient response of fuel cell - Ameerul A. J. Jeman; Naeem M. S. Hannoon; Nabil Hidayat; Mohamed M. H. Adam; Ismail Musirin; Vijayakumar V. (Bulletin of Electrical Engineering and Informatics, 2019)
This research work discusses a control strategy to enhance the transient response of the fuel cell and boost the real and reactive power flow from grid connected to fuel cell. The current output of the fuel cell depends on the availability of hydrogen in the fuel cell stack, a battery bank is implemented to supply the transient current and to prevent it from hydrogen saturation. The battery should only supply when there is a transient. During steady state the total power is produced by the fuel cell by regulating its hydrogen input. A prototype of the system will be created to study a control scheme which regulates the current from an input source and a battery which is connected to a dc motor. The control philosophy is based on d-q transformation and subsequently generating a reference signal that is tracked by an IGBT based inverter. The speed of the motor is controlled using pulse with modulation. The dynamic modeling of the standalone fuel cell that is connected to a dc motor is carried out using MATLAB/SIMULINK platform. The simulation results show that the control scheme works well, although the dynamic response of the system can be improved. The testing carried on the prototype proves that the concept works well, but a hydrogen control scheme should be developed to improve the efficiency of the control scheme.